On the feasibility of a 750 GeV complementary Higgs boson - Engel Roza (Results in Physics, 2016)
Summary: It is shown that the adoption of the Stueckelberg mechanism, as an alternative to the Spontaneous Symmetry Breaking mechanism, gives an adequate explanation for the recent reported signatures in LHC experiments at CERN, which points to the existence of a 750 GeV complementary boson next to the 125 GeV Higgs field boson. Keywords: Higgs mechanism, Stueckelberg mechanism, 125 GeV boson, 750 GeV boson